Gabriella Infinita: a perspective of Colombian history and culture through electronic literature - Perla Sassón-Henry (Texto Digital)
Gabriella infinita is a landmark of Latin American digital literature by Colombian author Jaime Alejandro Rodríguez Ruiz. It is a hypermedia novel in Spanish which was originally written and published as a traditional printed novel in 1994, to later on become a hypertext and a hypermedia novel. As a literary piece, Gabriella Infinita is an excellent example of Latin American literature. It brings to the fore topics that have been common to many Latin American countries, such as a civil war, guerrilla wars, repression, freedom of expression, fear and exile. It also highlights Latin America fascination with the United States and the counterculture movements of the 1970s. This essay explores how Colombian writer Jaime Alejandro Rodríguez Ruiz uses the various modalities of the new media in his hypermedia Gabriella Infinita to provide a better understanding of Colombian culture and history.